The Energy Politics of the European Union and the Possibility to Implement it in Post-Soviet States - Dudin, Mihail Nikolaevich; Zasko, Vadim Nikolaevich; Dontsova, Olesya Igorevna; Osokina, Irina Valentinovna (International Journal of Energy Economics and Policy, 2020)
The purpose of the work is to study the evolution of the energy politics of the European Union (the EU), and the possibility to apply such experience in the post-Soviet states. The goals stated in the European energy strategy probably cannot be fully achieved by 2020. The problem is the insufficient infrastructure development and the incomplete safety of energy innovations for the environment. However, the problem can be solved in the short-term run due to the social and environmental responsibility of corporations and by promoting “clean technology entrepreneurship”. It is impossible to use the EU energy politics provisions in the post-Soviet states. This will require large investments, and the population is not ready to move to the principles of energy conservation and energy efficiency. Post-Soviet countries need to reform the state energy and socio-economic policies rather than the energy sector. Keywords: energy politics, European Union, Russian Federation, CIS, renewable energy, energy intensity, energy efficiency, energy conservation. JEL Classifications: Q40, Q43, Q48. DOI: https://doi.org/10.32479/ijeep.9077